O museu de ciências como promotor da motivação: lembranças do público do setor de química do CDCC/USP - Guzzi, Mara Eugênia Ruggiero de (2014)
This work refers to a study of the motivational aspects found in the mini courses offered by the Chemistry Sector of the Center for Cultural and Scientific Dissemination (Centro de Divulgação Científica e Cultural CDCC). The self-determination theory was used as a reference to study the Science Museum potential to act as a motivational promoter, exploring activities that may propitiate situations that will involve intrinsically motivated visitors and also to understand how extrinsic stimuli can regulate self-determined forms of motivation. The data acquisition allowed the identification of the mini courses scenario influenced by Center s actions and ideology during its implantation and consolidation, by gathering information referent to the nature and conception of actions, public involvement, profile and impressions during the conduction of the mini courses and after a long gap. The study of the public was conducted with two groups with different characteristics: one of which involved the participants of a partnership between the CDCC and teaching students; the other group was constituted by an independent public with a diversified profile. The results and analysis obtained under different views (motivational profile, perception about the sense attributed to participation and interactions during the activities) brought some elements that confirm the emergence of situations capable of nurturing psychological needs of autonomy, competence and relationship. The nature and characteristics of the activities awakened the enthusiasm of the visitors in situations appropriated to the intrinsic involvement, i.e., moved by the personal satisfaction provided by the experience. It was also observed, however, that they can be extrinsically stimulated in activities that lead to the regulation that approaches self-determination. It was established that in a short gap after the participation in the activities, the experience was perceived as meaningful for both groups and after a twenty years gap, the motivational aspects were enhanced in the independent group that was more participant and assiduous in the museum. The results of this work suggest that nurturing the subjacent psychological needs is a way to fully explore scientific dissemination that does not exclude the missions assumed by the Institutions with the Science Museum, defining it as a nonformal teaching space that promotes self-determined forms of motivation.